2018
DOI: 10.1016/j.marenvres.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exposure to dispersed oil and burned oil residue on long-term survival, growth, and reproductive development in polar cod (Boreogadus saida)

Abstract: The present study investigates the potential long-term physiological effects on maturing polar cod (Boreogadus saida), an Arctic key species, after an acute exposure (48 h) to environmentally realistic concentrations of either mechanically dispersed oil (MDO), chemically dispersed oil (CDO) or burned oil residues (BO) (N = 58-60 per treatment). Following exposure, fish were monitored in a common tank supplied with clean water for a seven-month period coinciding with the period of reproductive development. Fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…However, Faksness et al (2012) did not report differences in the chemical oil profile prior and after the burning. Nonetheless, focusing on the water phase under untreated or burned oil slick, the present findings of reduced concentrations of target PAHs in burn residue LEWAF compared with untreated oil LEWAF is in agreement with results from previous studies (Bender et al 2018;Blenkinsopp et al 1996). However, it has to be considered that the decrease of target PAHs was mainly related to the semi-volatile naphthalene.…”
Section: Acute Toxicity Of Heavy Fuel Oil Compounds In Fish Embryossupporting
confidence: 92%
See 3 more Smart Citations
“…However, Faksness et al (2012) did not report differences in the chemical oil profile prior and after the burning. Nonetheless, focusing on the water phase under untreated or burned oil slick, the present findings of reduced concentrations of target PAHs in burn residue LEWAF compared with untreated oil LEWAF is in agreement with results from previous studies (Bender et al 2018;Blenkinsopp et al 1996). However, it has to be considered that the decrease of target PAHs was mainly related to the semi-volatile naphthalene.…”
Section: Acute Toxicity Of Heavy Fuel Oil Compounds In Fish Embryossupporting
confidence: 92%
“…The studies mainly have found a low toxic potential (Cohen et al 2005). However, also delayed effects after a recovery phase such as reproductive impact have been observed in fish that have been exposed to burn residues for a short period (Bender et al 2018). Using a comparable experimental setup as in the present study, Blenkinsopp et al (1996) focused on the toxicity of residues from the Newfoundland offshore burn experiment by preparing WAFs from the field residue samples and the (weathered) crude oil under laboratory conditions.…”
Section: Cewaf Ifo180mentioning
confidence: 91%
See 2 more Smart Citations
“…In the wake of the increased attention, climate change has attained in recent years (IPCC 2014(IPCC , 2019, and the increased sea temperatures that have already been observed in the Barents Sea and other arctic areas (Smedsrud et al 2013;ICES 2017ICES , 2018, the fate of polar cod and other true arctic species has become a theme of several research projects and research articles (Christiansen 2017;Kunz et al 2018;Bender et al 2018;Koenker et al 2018;Laurel et al 2018). The motivation for studying polar cod in the climate change context is driven by the fact that this species has a circumpolar distribution and in many of the areas where it occurs, it is the dominant pelagic species (Ajiad et al 2011;Bouchard et al 2017), playing a dominant role in those ecosystems (Lowry and Frost 1981;Bradstreet et al 1986;Orlova et al 2009;Hop and Gjøsaeter 2013;Mueter et al 2016).…”
Section: Introductionmentioning
confidence: 99%